The Impact of Digital Learning Technology Applications on the ‎Development of ‎Performance Skills Among University ‎Students‏ ‏ ‏ ‏ - Rami Khalil Jundi; Yasir Khalaf Rashid (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: The current research aims to identify the impact of digital learning technology ‎applications on developing performance skills among university students. ‎Methodology: To achieve the research objective, the semi-experimental approach ‎was adopted. The research sample was randomly selected, amounting to (380) male ‎and female students from Anbar University-Iraq. An observation card was also ‎prepared consisting of (15) sub-skills falling under five main areas: performance ‎skills (basic, social, mental, practical, and technological). Each area had three sub-‎skills. The validity and reliability of the tool was employed. Results: After ‎distributing the observation card to the instructors who teach the research sample ‎students, numbering (92) male and female instructors at Anbar University, to ‎measure (development of performance skills), and using appropriate statistical ‎methods, the results showed that digital learning technology applications have a ‎statistical significant impact on developing performance skills among university ‎students from the instructors' point of view. The results also showed that there is a ‎statistically significant difference according to the impact of digital learning ‎technology on developing performance skills among Anbar University students, and ‎that students have good general performance skills. There is also a statistically ‎significant difference between the students' averages according to the variable of ‎using digital learning technology applications; in favor of students who used the ‎applications. The results also indicated that there is a statistically significant ‎difference between the students' average grades according to the specialization ‎variable, in favor of the scientific specialization variable. Finally, the results also ‎showed that there is no statistically significant difference between the students' ‎averages according to the gender variable (male, female).‎